Towards Zero-Code Service Composition (Position paper) - Kiciman, Emre; Melloul, Laurence (The Eighth Workshop in Hot Topics in Operating Systems, 2001)
For many years, people have been trying to develop systems from modular, reusable components. The ideal goal is zero-code composition: building an application out of existing components without having to write code. By investigating zero-code composition, our goal is to make composition easy enough to be of practical use to systems reseawrchers and developers. We are focusing on identifying and removing systemic impediments to composition, and on exploiting composition to achieve system-wide properites, such as performance, scalability, and reliability.